Analisis Faktor-Faktor yang Berhubungan dengan Kepatuhan Pasien Tuberkulosis Paru Tahap Lanjutan Untuk Minum Obat di RS Rumah Sehat Terpadu Tahun 2015 - Wulandari, Dewi Hapsari (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
This research discussed on the This thesis aims to determine the factors that associated compliance patien lung Tuberculosis to swallowing drug at Rumah Sehat Terpadu Dompet Dhuafa Hospital 2015This research used mix methods approach with cross sectional design. This research found that there is still non compliances patient lung tuberculosis to swallowing medicine. The compliance is related on behavior (Predisposisi, Enabling, dan Reinforcing) and non behavior factor. To increase the compliance this research suggest to hospital support fot TB DOTS program, intens of counseling, support the PMO, availability of drug, and frequent recording dan reporting.